Exploring T Cell Reactivity to Gliadin in Young Children with Newly Diagnosed Celiac Disease. (3rd March 2014) - Liu, Edwin; McDaniel, Kristen; Case, Stephanie; Yu, Liping; Gerhartz, Bernd; Ostermann, Nils; Fankhauser, Gabriela; Hungerford, Valerie; Zou, Chao; Luyten, Marcel; Seidl, Katherine J.; Michels, Aaron W.
Abstract : Class II major histocompatibility molecules confer disease risk in Celiac disease (CD) by presenting gliadin peptides to CD4 T cells in the small intestine. Deamidation of gliadin peptides by tissue transglutaminase creates immunogenic peptides presented by HLA-DQ2 and DQ8 molecules to activate proinflammatory CD4 T cells. Detecting gliadin specific T cell responses from the peripheral blood has been challenging due to low circulating frequencies and heterogeneity in response to gliadin epitopes. We investigated the peripheral T cell responses to alpha and gamma gliadin epitopes in young children with newly diagnosed and untreated CD. Using peptide/MHC recombinant protein constructs, we are able to robustly stimulate CD4 T cell clones previously derived from intestinal biopsies of CD patients. These recombinant proteins and a panel of α - and γ -gliadin peptides were used to assess T cell responses from the peripheral blood. Proliferation assays using peripheral blood mononuclear cells revealed more CD4 T cell responses to α -gliadin than γ -gliadin peptides with a single deamidated α -gliadin peptide able to identify 60% of CD children. We conclude that it is possible to detect T cell responses without a gluten challenge or in vitro stimulus other than antigen, when measuring proliferative responses.